Surface modification of polystyrene beads by ultraviolet/ozone treatment and its effect on gelatin coating - Ahmad Nor, Yusilawati; Mel, Maizirwan; Mohd. Salleh, Hamzah; Ng , Kim Hong; Wong, Chiow San (Science Publications, 2010)
Polystyrene failed to provide any reactive functionality of surface hydrophilicity that is capable of binding proteins. It is known that polystyrene must be chemically modified to make its surface amenable to covalent crosslinking with protein. Approach: The aim of this study was to investigate the effects of UV/ozone treatment on gelatin coating. The surfaces of microsize polystyrene beads (150 μm) were modified by UV/ozone treatment system at different treatment time, ozone flow-rate and UV intensity was analyzed by Design expert software. The treated beads were characterized with ATR-FTIR analysis to determine the introduction of carbonyl (-C=O), carboxylic group (-COOH) and amide group (-CO-NH2) onto the polystyrene surface. Sample characterization was also carried out by SEM and densitometer. Gelatin immobilization was then preceded by incubating treated PS sample in gelatin solution and the total amount of gelatin coated on the modified surface was identified by Bradford assay. Results: The maximum amount of gelatin obtained was 63.75 μg mL-1 while the lowest amount obtained for untreated PS (9.947 μg mL-1). The introduction of carbonyl, hydroxyl and amide group on the polystyrene beads surface was confirmed by ATR-FTIR analysis and thus measures the importance of UV/ozone treatment. Conclusion: From the results, it has been found that time is the most significant factor to prepare samples for gelatin immobilization at reduced flow rate and at an increased Ultraviolet (UV) intensity in the ranges of study.